Kana Warrior: Teaching Hiragana To Malaysian Youth Using 2d Platformer Video Game - Marwan Shamon,; Rafidei Mohamad, (Journal of Computing Technologies and Creative Content, 2022)
The Japanese language is one of the most in-demand foreign languages in Malaysia. It is popular with the Malaysian youth because of the Japanese animation called Anime. It has influenced the youth to have an interest in the Japanese language. Since Japan’s economy is currently one of the largest globally, having proficiency in the Japanese language can be a boon to the youth. However, they do not actively study it despite having an interest in the language. Using gamification can effectively teach them the Japanese language. Hence, this research aims to develop a 2D platformer video game that teaches the Malaysian youth one of the writing scripts of the Japanese language, Hiragana. This research also aims to evaluate the effectiveness of the game among selected respondents. Another aim is to educate and motivate the Malaysian youth about the basics of Hiragana. This research uses the ADDIE Model which is commonly used to produce an effective design in the field of instructional design. An evaluation has been carried out to multiple respondents and they have given out positive feedback on the video game.